DeFalco, A. (2023). Curious kin in fictions of posthuman care. Oxford University Press - Sharma, Pummy (Journal of Posthumanism, 2024)
The crisis arising from climate change poses imminent threats to marginalised human and nonhuman populations, necessitating a concerted effort to formulate comprehensive solutions. The primary reason for climate change is humans’ rampant exploitation of natural resources through extractivism. The hubris of human exceptionalism allowed humans to continue this attitude of total disregard (Braidotti 2013, Ferrando 2020, Jensen and Auld 2022). In order to understand the flaws of human exceptionalism, it is imperative to comprehend prevailing notions of the human and how they create exclusionary boundaries.